Air pollution and surrounding greenness in relation to ischemic stroke: A population-based cohort study. (March 2022) - Avellaneda-Gómez, C.; Vivanco-Hidalgo, R.M.; Olmos, S.; Lazcano, U.; Valentin, A.; Milà, C.; Ambrós, A.; Roquer, J.; Tonne, C.
Graphical abstract: Highlights: Large population-based prospective cohort covering nearly the entire source population. Robust association between NO2 and incident ischemic stroke. Protective effect of residential surrounding greenness on ischemic stroke. No evidence of effect modification by age, socioeconomic status or smoking. Abstract: Background: Evidence for the association between environmental exposures and ischemic stroke (IS) is limited and inconsistent. We aimed to assess the relationship between exposure to air pollutants, residential surrounding greenness, and incident IS, and to identify population subgroups particularly sensitive to these exposures. Methods: We used data from administrative health registries of the public healthcare system in Catalonia, Spain to construct a cohort of individuals aged 18 years and older without a previous stroke diagnosis at 1st January 2016 (n = 3 521 274). We collected data on sociodemographic characteristics and cerebrovascular risk factors, and derived exposure at the participant's residence to ambient levels of fine particulate matter (PM2.5 ), black carbon (BC), nitrogen dioxide (NO2 ), and Normalized Difference Vegetation Index (NDVI) in a 300 m buffer as an indicator of greenness. The primary outcome was IS diagnosis at any point during the follow-up. We used Cox proportional hazards models to estimate associations between environmental exposures and incident IS and stratified analyses to investigate effect modification. Results: Between 1st January 2016 and 31st December 2017, 10 865 individuals were admitted to public hospitals with an IS diagnosis. Median exposure levels were: 17 µg/m 3 PM2.5, 35 µg/m 3 NO2, 2.28 µg/m 3 BC and 0.27 NDVI. Individuals with higher residential exposure to air pollution were at greater risk of IS: HR 1·04 (95% CI:0·99-1·10) per 5 µg/m 3 of PM2.5 ; HR 1.05 (95% CI:1·00-1·10) per 1 µg/m 3 of BC; HR 1·04 (95% CI:1·03-1·06) per 10 µg/m 3 of NO2 . Conversely, individuals with higher residential surrounding green space, had lower risk of IS (HR 0·84; CI 95%:0·7-1.0). There was no evidence of effect modification by individual characteristics. Conclusions: Higher incidence of IS was observed in relation to long-term exposures to air pollution, particularly NO2, in a region that meets European health-based air quality standards. Residential surrounding greenness was associated with lower incidence of IS.